2015
DOI: 10.1002/ase.1540
|View full text |Cite
|
Sign up to set email alerts
|

Frank Netter's legacy: Interprofessional anatomy instruction

Abstract: Several medical schools have recently described new innovations in interprofessional interactions in gross anatomy courses. The Frank H. Netter MD School of Medicine at Quinnipiac University in Hamden, CT has developed and implemented two contrasting interprofessional experiences in first-year medical student gross anatomy dissection laboratories: long-term, informal visits by pathologists' assistant students who work with the medical students to identify potential donor pathologies, and a short-term, formal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Fernandes and colleagues even reported a positive benefit to the students’ professional identity, as individuals 34 . Another group reported that having dental students involving in craniofacial anatomy actually improved the medical students’ motivation to learn and enhanced their perception of the importance of the subject matter in clinical practice 37 . Only Krause and colleagues reported partially negative student perceptions of interprofessional anatomy education 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Fernandes and colleagues even reported a positive benefit to the students’ professional identity, as individuals 34 . Another group reported that having dental students involving in craniofacial anatomy actually improved the medical students’ motivation to learn and enhanced their perception of the importance of the subject matter in clinical practice 37 . Only Krause and colleagues reported partially negative student perceptions of interprofessional anatomy education 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that using gross anatomy dissection as an IPE venue fosters positive attitudes toward other health professional students and enhances teamwork and communication skills 12,18,19. By identifying common grounds and complementarities in their knowledge of anatomy, students from different professional programs can better understand each other’s professional scope and improve their clinical collaboration 3,4,2022. Shields, Pizzimenti, Dudley‐Javoroski, Schwinn12 demonstrated that such activities between medicine and physical therapy programs successfully fostered discussions about each profession’s approach to learning about anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…However, for "competencies developed," when the data were not clear in the text of the article, we extracted them based on the similarity between the text and the competencies addressed by the Canadian Interprofessional Health Collaborative (CIHC) 17 and Interprofessional Education Collaborative (IPEC) 18 frameworks, and for remote activities, we used Gunawardena's interaction analysis model (AMI). 19 Regarding geographical distribution worldwide, nine of the included studies were conducted in North America, [20][21][22][23][24][25][26][27] five in South America, [28][29][30][31][32] three in Europe, [33][34][35] one in Africa, 36 and three in Oceania. [37][38][39] Figure 2 shows the universities involved.…”
Section: Resultsmentioning
confidence: 99%
“…The following undergraduate courses (mostly in the health sciences) were involved in the included articles: dentistry, 20,21-41 medicine, [21][22][23][24]27,[30][31][32][33][34]36,37,40,41 nursing, [20][21][22]25,26,[30][31][32][33]36,37,[39][40][41] pharmacy, 21,22,26,27,[30][31][32]36,37,40,41 physical education, 22,[30][31][32]39 occupational therapy, 22,27,36,37,39 nutrition, 22,23,…”
Section: Resultsmentioning
confidence: 99%